Atrial fibrillation is associated with left ventricular dysfunction and impaired myocardial energetics that persist despite catheter ablation: Is atrial fibrillation the chicken or the egg? - Wijesurendra, R; Liu, A; Eichhorn, C; Levelt, E; Ariga, R; Clarke, R; Rodgers, C; Bashir, Y; Ginks, M; Rajappan, K; Betts, T; Ferreira, V; et al. (BMJ Publishing Group, 2016)
Atrial fibrillation (AF) is associated with increased risk of heart failure and premature death, and is often resistant to treatment. Animal models of pacing-induced AF indicate that AF-induced endothelial dysfunction, impaired coronary reserve, and myocardial remodelling are important in arrhythmia maintenance. However, human AF may reflect a subclinical cardiomyopathy, which persists after sinus rhythm (SR) restoration and provides a substrate for AF recurrence. To test this hypothesis, we investigated the effect of restoring SR by catheter ablation on left ventricular (LV) function and energetics.